Maternal protein malnutrition: effects on prostate development and adult disease. (27th March 2018) - Rinaldi, J. C.; Santos, S. A. A.; Colombelli, K. T.; Birch, L.; Prins, G. S.; Justulin, L. A.; Felisbino, S. L.
Abstract: Well-controlled intrauterine development is an essential condition for many aspects of normal adult physiology and health. This process is disrupted by poor maternal nutrition status during pregnancy. Indeed, physiological adaptations occur in the fetus to ensure nutrient supply to the most vital organs at the expense of the others, leading to irreversible consequences in tissue formation and differentiation. Evidence indicates that maternal undernutrition in early life promotes changes in key hormones, such as glucocorticoids, growth hormones, insulin-like growth factors, estrogens and androgens, during fetal development. These alterations can directly or indirectly affect hormone release, hormone receptor expression/distribution, cellular function or tissue organization, and impair tissue growth, differentiation and maturation to exert profound long-term effects on the offspring. Within the male reproductive system, maternal protein malnutrition alters development, structure, and function of the gonads, testes and prostate gland. Consequently, these changes impair the reproductive capacity of the male offspring. Further, permanent alterations in the prostate gland occur at the molecular and cellular level and thereby affect the onset of late life diseases such as prostatitis, hyperplasia and even prostate cancer. This review assembles current thoughts on the concepts and mechanisms behind the developmental origins of health and disease as they relate to protein malnutrition, and highlights the effects of maternal protein malnutrition on rat prostate development and homeostasis. Such insights on developmental trajectories of adult-onset prostate disease may help provide a foundation for future studies in this field.